2012
DOI: 10.1111/j.1440-1746.2011.07045.x
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variation in PNPLA3 but not APOC3 influences liver fat in non‐alcoholic fatty liver disease

Abstract: Genetic variants in PNPLA3 but not APOC3 contribute to the variance in liver fat content due to NAFLD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
43
3

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(47 citation statements)
references
References 22 publications
1
43
3
Order By: Relevance
“…Later, Petersen et al [106] further demonstrated that the polymorphisms of ApoC3 (C-482T and T-455C) are associated with NAFLD and insulin resistance in Indian men. However, there is a contrary report suggested that the genetic variants in ApoC3 does not contribute to NAFLD in Finnish populations [107] . The reason regarding the divergent results remains unknown but importantly highlighted the ethnic differences in disease susceptibility.…”
Section: Genes That Affect Lipolysismentioning
confidence: 82%
See 1 more Smart Citation
“…Later, Petersen et al [106] further demonstrated that the polymorphisms of ApoC3 (C-482T and T-455C) are associated with NAFLD and insulin resistance in Indian men. However, there is a contrary report suggested that the genetic variants in ApoC3 does not contribute to NAFLD in Finnish populations [107] . The reason regarding the divergent results remains unknown but importantly highlighted the ethnic differences in disease susceptibility.…”
Section: Genes That Affect Lipolysismentioning
confidence: 82%
“…Hyysalo et al [107] 2012 ApoC3 polymorphism does not associated with NAFLD in Finnish populations GCKR Santora et al [108] 2012 GCKR polymorphism is associated with NAFLD Lipogenesis pathway plays a role in NAFLD pathogenesis Tan et al [112] 2013…”
Section: Pnpla3mentioning
confidence: 99%
“…Moreover, among Finnish subjects, APOC3 variants were not associated with liver fat content due to NAFLD [31]. The prevalence of variant APOC3 alleles was found to be 79.7% in Asian Indian, 66.8% in Italian, and 80% in Finnish individuals [29][30][31].…”
Section: Apolipoprotein C3 (Apoc3)mentioning
confidence: 86%
“…In contrast, in Italy and the United Kingdom, the APOC3 wild-type genotype was associated with a more favorable lipid profile but not with insulin resistance, NASH, or increased fibrosis [30]. Moreover, among Finnish subjects, APOC3 variants were not associated with liver fat content due to NAFLD [31]. The prevalence of variant APOC3 alleles was found to be 79.7% in Asian Indian, 66.8% in Italian, and 80% in Finnish individuals [29][30][31].…”
Section: Apolipoprotein C3 (Apoc3)mentioning
confidence: 87%
“…In comparison, other studies included larger proportions of persons with overweight/obesity, dyslipidemia and even full blown metabolic syndrome. For instance, in the Finnish study under discussion, 10 subjects with wild-type and variant alleles of APOC3 had mean BMI of 32 and 31.5 kg/m 2 , mean waist circumferences of 106 and 103 cm, and prevalence rates of metabolic syndrome of 68% and 62%, respectively. The failure to find an association between APOC3 variants and NAFLD in one large study even when only persons with BMI < 25 kg/m 2 were analyzed militates against this explanation; 6 however, in that study, the presence of visceral obesity, which may be present despite normal BMI, was not specifically looked for.…”
mentioning
confidence: 99%